Oculofacial alterations in NBAS-SOPH like mutations: Case report. Issue 2 (March 2020) - Nucci, Francesca; Lembo, Andrea; Farronato, Marco; Farronato, Giampietro; Nucci, Paolo; Serafino, Massimiliano
Purpose: To describe the clinical features of a rare case of NBAS-SOPH-like mutations; to emphasize special aspects of the ocular and oro-facial regions. Methods: Case report. Case Description: We present a 5-year-old girl initially examined for her dysmorphic features, mental delay, strabismus, and high myopia. During the funduscopic examination, we observed optic atrophy with narrow thinned arterioles with the light brown reflex of the central retina. A genetic assessment revealed NBAS-SOPH like mutation. An assessment by a team of orthodontists defined typical characteristics. Conclusions: NBAS mutations can also cause complex disease with a broad clinical spectrum ranging from isolated recurrent acute liver failure (RALF) to a multisystemic phenotype. Due to the heterogeneity of the expressions, a multispeciality approach to this situation is recommended.